'We Are a Modern Navy': Abolishing the Royal Navy's rum ration. Issue 1 (2nd January 2017) - Moore, Richard
Abstract : The Royal Navy's daily ration of free rum to sailors was abolished in 1970. Abolition was never justified on cost grounds, unlike so many other British defence decisions. Rather, rum was no longer in keeping with a navy of guided missiles and sensitive electronics. The decision was nevertheless many years in the making. The views of officers, ratings and doctors were gathered and officials dealt across Whitehall and with ministers, press and parliament. Eventually, abolition was an idea whose time had come. This article explores the key steps and key personalities behind a significant milestone in the social history of the Royal Navy.